Monocyte Chemoattractant Protein-1 −2518 A/G Single Nucleotide Polymorphism Might Be Associated with Renal Disease and Thrombocytopenia of SLE. (21st April 2010) - Piotrowski, Piotr; Lianeri, Margarita; Gasik, Robert; Roszak, Andrzej; Olesińska, Marzena; Jagodziński, Paweł P.
Abstract : There is conflicting evidence on the contribution of the MCP-1 −2518 A>G (rs 1024611) polymorphism to SLE incidence and clinical manifestations. We examined the prevalence of the MCP-1 −2518 A>G polymorphism in SLE patients (n = 199 ) and controls (n = 250 ) in Poland. We did not observe a significant difference in the distribution of MCP-1 −2518 A>G polymorphic variants in patients with SLE and healthy individuals. However, we found an association between the GG versus AG and AA genotypes as well as the AG and GG versus AA genotypes with renal manifestations of SLE OR = 3.614 (1.123–11.631, P = 0.0345 ) and OR = 2.297 (1.301–4.057, P = 0.0046 ), respectively. We also observed that the MCP-1 AG and GG -genotypes contribute to the occurrence of thrombocytopenia in SLE patients OR = 2.618 (1.280–5.352, P = 0.0089 ). Our observations indicate that either MCP-1 −2518 G variant can be associated with some clinical findings in patients with SLE.